Who is Susceptible to Nudge? Nudge Susceptibility Clusters of Physical Activity in a College Setting - Wang, Xinghua; Song, Guandong; Wan, Xia (Technium Social Sciences Journal, 2022)
Currently, the settings of higher education system have made inactivity lifestyle already as social norms on campus. The World Health Organization encouraged to promote physical activity behaviors by setting-based approaches. Nudges could improve physical activity behaviors by changing college settings. However, not everyone could be “Nudgeable”. Finding the “High-Nudgeable” people would help the policymakers to understanding who can be nudged effective among the population. In the present study, we measured the susceptibility of physical activity nudges in a college setting by CPANSS. Based on the overall mean value of nudge susceptibility of five nudge types, we classified the degree of overall “Nudgeable” into “Low-Nudgeable”, “Medium-Nudgeable” and “High-Nudgeable” by a k-means non-hierarchical cluster analysis. This study conducted the target group index (TGI) to determine the demographic attributes (gender, major, and grade) of “High-Nudgeable” college students, and the findings indicated that individuals with following demographic attributes are nudgeable in a high level, which are female (TGI=124.29), be major in social science (TGI=105.02), medical (TGI=127.52) and sports (TGI=103.67), and in Grade 1 (TGI=118.88).